Qur'anic Stylistics: A Heart-Calming Surah - Fadila, Miftah; Sopian, Asep; Saleh, Nalahuddin (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
The Qur'an is a holy book with a beautiful arrangement of words and sentences and deep meaning. It must be adequately understood in order to get to the intended meaning; it requires a linguistic approach, one of which is stylistics, which can explain the relationship between language and its artistic functions and meanings and create an impression on each of them, surah Ad-Dhuha was chosen because there are several mistakes in understanding it and has beauty in the harmony of the verses and the selection of each word and sentence. This research analyzes surah Ad-Dhuha using a stylistic perspective that includes phonology, morphology, and syntax. The purpose of this research is to know and reveal the use of language and the aesthetic aspects and meanings contained in surah Ad-Dhuha. The method used in this research is a qualitative approach using content analysis. This research is expected to contribute to expanding the understanding of the Quran, especially surah Ad-Dhuha, and increasing the appreciation of its aesthetic elements. The results of this study are 1) Surah Ad-Dhuha has a perfect stylistic aesthetic, both in terms of sounds, words, and sentences, 2) the selection of plosive consonant sounds that are more than just fricative sounds, according to the meaning contained in them, 3) according to the morphological aspect, it was found that the selection of fi'il, be it madhi, mudhari' or amar, has a specific intention to strengthen the meaning to be conveyed, 4) according to the syntax aspect, it is also found that the selection of elements that compose it also aims to strengthen the meaning of surah Ad-Dhuha such as the letter qasam, fa'il, and the use of maf'ul bih.